Lymphatic Territories (Lymphosomes) in Swine. Issue 2 (August 2015) - Ito, Ran; Suami, Hiroo
<x xml:space="preserve">Abstract</x> Background: The swine is a common preclinical large-animal model for medical research because of the resemblance of its tissue structures to those of humans. However, the lymphatic system in swine is poorly understood. The authors investigated the lymphatic system and defined territories (lymphosomes) in swine using the microinjection technique. Methods: Six swine (two male and four female 17.5- to 50-kg Sus domesticus) were used. Real-time indocyanine green fluorescence lymphography was performed in four live swine. After the animals were killed, the authors injected a radiocontrast mixture consisting of barium sulfate and hydrogen peroxide with red acrylic dye directly into lymphatic vessels in six swine carcasses. Courses of the lymphatic vessel were analyzed radiographically. The lymphatic vessels were dissected meticulously and chased until they connected to the first-tier (sentinel) lymph node. This procedure was repeated throughout the body until all the relationships between the lymphatic vessels and lymph nodes were defined. Results: The authors successfully mapped the superficial lymphatic vessels and their corresponding lymph nodes. Indocyanine green fluorescence lymphography and subsequent radiography revealed that the swine lymphatic system contained seven lymphosomes: parotid, mandibular, dorsal cervical, ventral cervical, subiliac, inguinal, and popliteal territories. Of note, no lymph nodes existed in the superficial axillary region. Conclusions: The swine could be a useful large-animal model for lymphatic research because of the anatomical consistency of the lymphosomes among animals and the sizable lymphatic vessels. However, swine lack the superficial axillary lymph node found in humans, suggesting that swine may not be a good model for breast cancer–related lymphedema.